Fecal microbiota transplantation for ulcerative colitis: a prospective clinical study - Tian, Yan; Zhou, Yan; Huang, Sisi; Li, Jun; Zhao, Kui; Li, Xiaohui; Wen, Xiangchen; Li, Xiao-an (BMC gastroenterology, 2019)
Fecal microbiota transplantation may contribute to disease remission in ulcerative colitis; however, the factors that determine the effects of treatment remain unknown. The aim of the present study was to prospectively investigate the clinical efficacy of fecal microbiota transplantation in patients with ulcerative colitis and identify the bacterial signatures associated with clinical remission. A total of 20 patients with ulcerative colitis were included in this prospective and uncontrolled study. All patients underwent gastroscopy five times, once every 3 weeks. Clinical indices were used to assess the efficacy of fecal microbiota transplantation, as well as the Mayo score, a score used to evaluate the extent of intestinal mucosal lesions in patients with ulcerative colitis. The changes in intestinal flora were detected by 16S ribosomal RNA-sequencing, and the relationship between ulcerative colitis and intestinal flora was analyzed. After treatment, clinical index scores for diarrhea, abdominal pain, and blood stool decreased significantly (p < 0.05). Erythrocyte sedimentation rate and C-reactive protein levels had not changed significantly; however, the clinical index score for intestinal mucosal lesions and the Mayo score decreased significantly. In addition, 16S ribosomal RNA-sequencing revealed that the intestinal flora in patients diagnosed with ulcerative colitis was different from that of donors. Fecal microbiota transplantation has a potential therapeutic value for the treatment of ulcerative colitis as it changes the abundance of bacterial flora and improves the scores for diarrhea, abdominal pain, and mucous membrane lesions in patients with this disease. The clinical trial was retrospectively registered with ClinicalTrials.gov ( NCT03016780 ) on January 11th, 2017.